2015
DOI: 10.1016/j.cj.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mapping of QTLs on chromosome 2D for grain size and yield traits using a mutant line induced by EMS in wheat

Abstract: Production of mutants with altered phenotypes is a powerful approach for determining the biological functions of genes in an organism. In this study, a high-grain-weight mutant line M8008 was identified from a library of mutants of the common wheat cultivar YN15 treated with ethylmethane sulfonate (EMS). F 2 and F 2:3 generations produced from crosses of M8008 × YN15 (MY) and M8008 × SJZ54 (MS) were used for genetic analysis. There were significant differences between M8008 and YN15 in plant height (PH), spike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 33 publications
9
24
0
Order By: Relevance
“…233 al., 2013). Only few studies are available based on digital image analysis of grain size and shape in bread wheat (Williams et al, 2013;Gegas et al, 2010;Williams and Sorrells, 2014;Breseghello and Sorrells, 2007;Xiao et al, 2011;Rasheed et al, 2014;Zhang et al, 2015). Among these studies, Gegas et al, 2010;Williams et al (2013), Williams and Sorrells (2014) and Rasheed et al (2014), used shape variations as targeted traits influencing grain size and weight and results are comparable to our work.…”
Section: Cluster Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…233 al., 2013). Only few studies are available based on digital image analysis of grain size and shape in bread wheat (Williams et al, 2013;Gegas et al, 2010;Williams and Sorrells, 2014;Breseghello and Sorrells, 2007;Xiao et al, 2011;Rasheed et al, 2014;Zhang et al, 2015). Among these studies, Gegas et al, 2010;Williams et al (2013), Williams and Sorrells (2014) and Rasheed et al (2014), used shape variations as targeted traits influencing grain size and weight and results are comparable to our work.…”
Section: Cluster Analysissupporting
confidence: 78%
“…The high significant differences (P < 0.001) among genotypes for all traits indicating the presence of adequate variability among the bread wheat local landraces which can be used for the improvement of grain weight and quality in order to create high yielding varieties with good end-use quality. Though compare the measures for traits such as grain size and shape in different studies because of different approaches to converting raw images into quantitative data is not completely correct, differences between high and low level for the most traits in this study are more in compared with other studies such as Sun et al (2009),Tsilo et al (2010, Jia et al (2013) and Zhang et al (2015). Due to the high diversity, it seems can find suitable genotypes with high and low limit bounds for two or more traits as versus each other.…”
Section: Cluster Analysismentioning
confidence: 43%
“…In addition, there are many reports of QTLs for TKW on chromosome 1B 1,7,27,28 . However, previous studies have found QTLs for TKW on almost all chromosomes of the wheat genome 1,2,[6][7][8][10][11][12][13]25,[27][28][29][30][31][32][33][34][35] . Kernel-related traits are susceptible to environmental impact, and the observed values of the same plant materials in different environments were also significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic changes in plant induced mutation with EMS can be caused by mutagenesis mechanism which a G/C to A/T nucleotides change in the primer binding regions of SSR marker [23,24,25]. In addition, insertion or deletion of nucleotide in the DNA sequences of mutant plants inducing the lengthening or shortening repeat region of microsatellite marker [24,26,27].…”
Section: Genetic Relationship Of Ems-induced Chili Pepper Mutants Andmentioning
confidence: 99%